Linking Green HRM Practices and Green Innovation to Sustainable Performance: Evidence from Upscale Hotels in India - Ashraf, Aaliya; Andrabi, Ulfat; Khalid, Syed Mohd; Popescu, Virgil; Birau, Ramona; Nioata (Chireac), Roxana-Mihaela; Lupu (Filip), Gabriela Ana Maria (International Journal of Accounting and Economics Studies, 2025)
This study examines green innovation, green HRM bundle practices, and Triple Bottom Line sustainability performance. A tailored survey will quantify the data of 305 high-end hotel personnel in Punjab and Uttar Pradesh. Smart PLS used structural equation modeling to analyze data. Data show that green HRM package practices improve hotels’ sustainability. Green innovation also has a significant impact on sustainable performance and partially mediates the relationship between green HR practices and SMEs’ sustainable performance. This study advises using GHRM to improve hotels’ GI adoption and sustainability. This study reinforces conventional wisdom. Innovation and human resources environmental management techniques can improve sustainability.